Construction of reusable fluorescent assembled 3D-printed hydrogen-based models to simulate minimally invasive resection of complex liver cancer. - Wenli Cao; Xiaofeng Pan; Liming Jin; Jie Liu; Jie Cao; Lei Jin; Fangqiang Wei (PLoS ONE)
Complex liver cancer is often difficult to expose or dissect, and the surgery is often challenging. 3D-printed models may realistically present 3D anatomical structure, which has certain value in planning and training of liver surgery. However, the existing 3D-printed models are all monolithic models, which are difficult to reuse and limited in clinical application. It is also rare to carry fluorescence to accurately present tumor lesions. Here we report reusable fluorescent assembled 3D-printed models to mimic minimally invasive resection of complex liver cancer. Based on the models, multiple copies of liver lesion structure assembled accessories can be printed for the same patient or different patients, ensuring the quantity and quality of simulated surgical training, and greatly reducing the cost of simulated surgical training. The addition of fluorescence is helpful in accurately presenting tumor lesions. The reusable fluorescent assembled 3D-printed models may mimic minimally invasive resection of complex liver cancer, demonstrating potential value in simulated surgery.